Il sistema degli spazi pubblici di Siviglia: dalla pianificazione alla gestione - Antonio García García (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The debate around the management of public space has become, in the last decades, one fundamental theme of the debate around the city. Nevertheless, there is an imbalance between the consensus of many theoretical approaches and the application of these on projects and urban plans, except for some paradigmatic cases. Through the case of Seville, the article goes into some issues of systems of public spaces: its cartographic representation, its hierarchic structure or the value of understanding the real scope of each space. All from the perspective of the importance of integrating physical and human planning in the management of these spaces, whose last sense is the sociability.